Diagnostic and perinatal outcomes in consanguineous couples with a structural fetal anomaly: A cohort study. (27th November 2020) - Mone, Fionnuala; Doyle, Samantha; Ahmad, Asfa; Abu Subieh, Hala; Hamilton, Susan; Allen, Stephanie; Marton, Tamas; Williams, Denise; Kilby, Mark D.
Abstract: Introduction: Consanguineous unions occur when a couple are related outside marriage and is associated with adverse genetic and perinatal outcomes for affected offspring. The objectives of this study were to evaluate: (i) background characteristics, (ii) uptake of prenatal and postnatal investigation and (iii) diagnostic outcomes of UK consanguineous couples presenting with a fetal structural anomaly. Material and methods: This was a retrospective and partly prospective cohort study comparing consanguineous (n = 62) and non‐consanguineous (n = 218) pregnancies with current or previous fetal structural anomalies reviewed in a UK prenatal genetic clinic from 2008 to 2019. Outcomes were compared using odds ratios (OR). Results: Most consanguineous couples were of Pakistani ethnicity (odds ratio [OR] 29, 95% confidence interval [95% CI] 13‐62) and required use of an interpreter [OR 9, 95% CI 4‐20). In the consanguineous group, the uptake of prenatal invasive testing was lower (OR 0.4, 95% CI 0.2‐0.7) and the number declining follow up was greater (OR 10, 95% CI 3‐34) than in the non‐consanguineous group. This likely explained the lower proportion of consanguineous couples where a final definitive unifying diagnosis to explain the fetal structural anomalies was reached (OR 0.3, 95% CI 0.2‐0.6). When a diagnosis was obtained in this group, it was always postnatal and most often using genomic sequencing technologies (OR 6, 95% CI 1‐27). The risk of perinatal death was greater (OR 3, 95% CI 1‐6) in the consanguineous group, as was the risk of fetal structural anomaly recurrence in a subsequent pregnancy (OR 4, 95% CI 1‐13). There was no difference in the uptake of perinatal autopsy or termination of pregnancy between groups. Conclusions: Consanguineous couples are a vulnerable group in the prenatal setting. Although adverse perinatal outcomes in this group are more common secondary to congenital anomalies, despite the evolution of genomic sequencing technologies, due to a lower uptake of prenatal testing it is less likely that a unifying diagnosis is obtained and recurrence can occur. There is a need for proactive genetic counseling and education from the multidisciplinary team, addressing language barriers as well as religious and cultural beliefs in an attempt to optimize reproductive options.